2020
DOI: 10.1029/2019je006042
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Budgets of Giant Impacts

Abstract: Giant impacts dominate the final stages of terrestrial planet formation and set the configuration and compositions of the final system of planets. A giant impact is believed to be responsible for the formation of Earth's Moon, but the specific impact parameters are under debate. Because the canonical Moon-forming impact is the most intensely studied scenario, it is often considered the archetypal giant impact. However, a wide range of impacts with different outcomes are possible. Here we examine the total ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…Stirring and disruption during the giant impact and inside the protolunar disk can bring large parts of the silicates mantle and of the impactor's core in contact with each other. As our results and previous work (Carter et al, 2020;Nakajima and Stevenson, 2015) show there is a large entropy gain during the impact, it is conceivable that the temperature rise due to this gain is enough to enhance the mixing of lithophile elements with iron metal, which subsequently increase the lithophile element content of the Earth's core. This would boost the mantle-core chemical exchange and equilibration from an early stage and provide the necessary initial state from which chemical unmixing can proceed to fuel the first stages of the dynamo, as was suggested in experiments recording the exsolution of various lithophile components from the liquid core (Badro et al, 2016;Hirose et al, 2017).…”
Section: Vaporization During the Giant Impactsupporting
confidence: 76%
See 1 more Smart Citation
“…Stirring and disruption during the giant impact and inside the protolunar disk can bring large parts of the silicates mantle and of the impactor's core in contact with each other. As our results and previous work (Carter et al, 2020;Nakajima and Stevenson, 2015) show there is a large entropy gain during the impact, it is conceivable that the temperature rise due to this gain is enough to enhance the mixing of lithophile elements with iron metal, which subsequently increase the lithophile element content of the Earth's core. This would boost the mantle-core chemical exchange and equilibration from an early stage and provide the necessary initial state from which chemical unmixing can proceed to fuel the first stages of the dynamo, as was suggested in experiments recording the exsolution of various lithophile components from the liquid core (Badro et al, 2016;Hirose et al, 2017).…”
Section: Vaporization During the Giant Impactsupporting
confidence: 76%
“…As the predicted pressure thresholds for vaporization can be easily reached, a large amount of iron receives enough entropy to vaporize. The entropy threshold can even be easier exceeded due to the entropy gain after the first and secondary shocks and the conversion of gravitational potential energy to internal energy (Carter et al, 2020;Nakajima and Stevenson, 2015). Once again during this process the confinement of core fragments by the surrounding mantle may prohibit the isentropic expansion and thus the vaporization.…”
Section: Vaporization During the Giant Impactmentioning
confidence: 99%
“…The highest pressure and temperature conditions for core formation likely occur during and in the aftermath of giant impacts. As discussed above, in such events much of the core of the impacting body may not equilibrate efficiently with the proto‐Earth's mantle (i.e., k ≪ 1, e.g., Carter et al., 2020; Landeau et al., 2016) and Earth's core likely inherited a strong memory of its earlier accretion. Therefore, the effect of core formation on the composition of Earth's mantle and core cannot be accurately determined using an “average” pressure and temperature of equilibration, as has often been done (e.g., Chidester et al., 2017), and the complicated dynamics of metal‐silicate partitioning in accretionary processes must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This study was motivated by the density disparity observed in exoplanet systems. The post-impact bodies in our simulations are hot and inflated, often with a large mass of vaporised silicate, and thus do not represent the structure of planets millions of years after their final giant impacts (Lock & Stewart 2017;Carter et al 2020;Lock et al 2020).…”
Section: Discussionmentioning
confidence: 99%